Heritage awareness among Singaporeans. - Low, Bee Wah. (2008)
The aim of study is to find out the level of understanding, awareness and participation on cultural heritage among young Singaporeans. The SWOT technique is also used to analyze the current situation on creating heritage awareness among young Singaporeans.